Allen Ginsberg in India: life and narrative - Rath, Akshaya K. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article deals with Allen Ginsberg`s ?Indian Journals? and later poems and argues that Ginsberg domesticates Indian gods and goddesses to castigate American capitalism . After bringing American poetry out into the streets, Ginsberg takes refuge in Indian cultural heritage, and contemporizes its religious myths ?to return to America to confront the nation at war?.
Keywords: Ginsberg, Irwin Allen (1926-1997); "Indian Journals"; religion; myth; capitalism